Standards-based mathematics reforms and mathematics achievement of American Indian/Alaska Native eighth graders. - Akiba, Motoko; Chiu, Ya-Fang; Zhuang, Yue-Lin; Mueller, Heather E. (Education Policy Analysis Archives, 2008)
Using the NAEP nationally-representative data collected from eighth-graders, we investigated the relative exposure of American Indian/Alaska Native (AIAN) students to mathematics teachers who are knowledgeable about standards, participate in standards-based professional development, and practice standards-based instruction; American Indian/Alaska Native student reports of standards-based classroom activities; and how student reports of classroom activities and teacher reports of their knowledge, professional development, and practices are associated with mathematics achievement of American Indian/Alaska Native students. We found that AIAN students had among the lowest exposure to teachers who reported they were knowledgeable about standards, who participated in standards-based professional development, and who practiced standards-based instruction. In addition, AIAN students were less likely than African American and Latino students to report that they experienced standards-based classroom activities. Our data showed that teacher reports of standards-based knowledge and practice of standards-based instruction were not significantly associated with mathematics achievement of AIAN students. However, student reports of classroom activities characterizing standards-based instruction was associated with higher mathematics achievement of AIAN students.